IMPLEMENTASI MANAJEMEN PERGURUAN TINGGI DI ERA MODERN (Studi Transformatif pada STKIP PGRI Bandar Lampung) - Istiara, Febriyantina; Jaya, Wayan Satria (Lentera: Jurnal Ilmiah Kependidikan, 2018)
In Indonesia, the human development index (HDI), which measures the comparison between life expectancy, literacy, education, and standard of living has not risen significantly. Conditions of participation to continue in college is still low when compared with countries in Southeast Asia. Amid the conditions of education in Indonesia as it is today, STKIP PGRI Bandar Lampung which is one of the largest Private Universities (PTS) in Lampung is encouraged not to cease to organize the arrangement of educational system so that it becomes the center of excellence of the various things that people need emphasizes Quality, Efficiency, and Relevance in making it a real college that relies excellence and professionalism, as well as vision, mission, and objectives. The vision and mission of the university reflects intrinsic quality with a multi-faceted and multidimensional approach.